Boron-doped diamond film / metal composite electrode and preparation method thereof
By preparing a micro -boron -mixed diamond film with a micro -structure and compound metal that matches the energy level, the problem of conductivity and stability in marine salinity measurement is difficult to coordinate and improve in the marine salinity measurement. Essence
Patent Information
- Application Number
- CN202411899893.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-28
Smart Images

Figure CN119372620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal / non-metal composite electrode preparation, and in particular to a boron-doped diamond film / metal composite electrode and a preparation method thereof. Background Art
[0002] Salinity is an important parameter for studying the physical and chemical processes of seawater, and has important guiding significance for marine science research, marine chemical industry, aquaculture, ecological network survey, seawater climate monitoring, marine energy exploration and development, and military defense. However, due to insufficient research on marine sensor materials, 90% of the domestic market share of high-end marine salinity sensors currently relies on imports, which seriously restricts the development of my country's marine science and technology.
[0003] At present, platinum black electrodes are the main commercial electrodes for salinity detection due to their low polarization impedance and ideal electrical properties. However, the deposited platinum black layer is extremely fragile and the deposition process has poor repeatability. It is difficult to work stably for a long time in a complex marine environment with the interaction of wind, waves, currents, tides, surges, electrochemical corrosion and biological attachment. Although foreign salinity sensors have high accuracy, most of them use platinum black electrodes, which need to be replaced every year. Boron-doped diamond film materials have excellent properties such as wide electrochemical window, low background current, stable physicochemical properties, high mechanical strength and strong corrosion resistance. They can meet the needs of long-term stable operation of ocean salinity and have good application prospects in the field of ocean salinity sensing. However, boron-doped diamond thin film electrodes are semiconductor materials with lower electrical conductivity than metal materials. In the salinity measurement system, the electrode equivalent resistance is relatively large. In order to achieve higher precision measurements, the boron doping amount of the boron-doped diamond film is often increased to effectively improve the carrier concentration and conductivity of the material. However, heavy boron doping easily introduces non-diamond carbon, which destroys the stability of the surface of the boron-doped diamond thin film electrode, increases the electrode background current, and limits the improvement of the performance of the boron-doped diamond thin film electrode.
[0004] Therefore, the problem that the conductivity and stability of boron-doped diamond films cannot be improved synergistically, and the problem that the contact resistance of boron-doped diamond films and metal composites affects conductivity, need to be solved simultaneously in the process of studying seawater salinity measurement. Summary of the invention
[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a composite electrode and a preparation method thereof which can simultaneously solve the stability and conductivity problems of a boron-doped diamond thin film electrode and improve the accuracy of salinity measurement.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a boron-doped diamond film / metal composite electrode, comprising the following steps: Step 1: Preparation of heavily boron-doped diamond film, using hot wire chemical vapor deposition equipment to adjust growth parameters, and after a certain growth time, obtain a heavily boron-doped diamond film with a large amount of non-diamond carbon on the surface; Step 2: treating the surface of the heavily boron-doped diamond film, removing non-diamond carbon by etching, and obtaining a boron-doped diamond film with a surface microstructure; Step 3: Energy level matching metal fills the surface microstructure, calculates the energy band structure of the boron doped diamond film and the energy level matching with the metal, deposits an energy level matching metal film on the surface of the boron doped diamond film with surface microstructure and performs high temperature heat treatment to obtain a boron doped diamond film / metal composite electrode with a smooth structure surface.
[0007] The above-mentioned method for preparing the boron-doped diamond film / metal composite electrode also includes step 4: testing the electrical and ocean salinity sensing performance of the boron-doped diamond film / metal composite electrode, testing the conductivity, contact resistance, and electrical properties of the boron-doped diamond film / metal composite electrode.
[0008] The preparation method of the above-mentioned boron-doped diamond film / metal composite electrode comprises the following steps: measuring the conductivity of the boron diamond metal composite electrode using a four-probe measuring instrument; measuring the contact resistance between the boron diamond metal composite electrode and the metal using a probe station; and analyzing the electrical properties of the boron diamond metal composite electrode using an electrochemical workstation with the boron diamond metal composite electrode as a working electrode and metal platinum as a counter electrode.
[0009] The method for preparing the boron-doped diamond film / metal composite electrode, step 1 comprises: Step 1-1: Clean the hot wire chemical vapor deposition equipment chamber, place the tantalum wire on the bracket, place the substrate on the base plate, close the chamber, and evacuate to below 10Pa; Step 1-2: adjusting the amount of methane and hydrogen introduced into the chamber to carbonize the tantalum wire; Step 1-3: adjusting the flow ratio of trimethylborane to methane into the chamber, maintaining the pressure balance in the chamber, maintaining the flow rate of hydrogen, controlling the growth temperature at 850-900° C., and growing a boron-doped diamond film in the chamber; Step 1-4: reducing the hydrogen flow rate to obtain a heavily boron-doped diamond film containing non-diamond carbon on the surface.
[0010] In the above-mentioned method for preparing the boron-doped diamond film / metal composite electrode, the step 2 of treating the surface of the heavily boron-doped diamond film comprises an immersion treatment method and / or an etching treatment method.
[0011] The above-mentioned method for preparing the boron-doped diamond film / metal composite electrode, the immersion treatment method comprises: Step 2-1: Acid mixing: Mix concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1 to 1:3, and heat to 260-300°C; Step 2-2: soaking treatment, soaking the grown boron-doped diamond film in a sulfuric acid and nitric acid mixed acid solution for 2-4 hours to remove non-diamond carbon on the surface; Step 2-3: Surface cleaning: soak the soaked boron-doped diamond film in deionized water, treat it with an ultrasonic cleaner for 20-40 minutes, and blow dry it with nitrogen to obtain a boron-doped diamond film with a surface microstructure.
[0012] The above-mentioned method for preparing the boron-doped diamond film / metal composite electrode, the etching treatment method includes: placing the heavily boron-doped diamond film into a plasma etcher, introducing oxygen and argon into the plasma etcher, the oxygen and argon flow ratio is 5:1 to 10:1, adjusting the power of the plasma etcher, treating for 10-30 minutes, removing non-diamond carbon on the surface of the heavily boron-doped diamond film, and forming a boron-doped diamond film with a microstructure on the surface.
[0013] In the above-mentioned method for preparing the boron-doped diamond film / metal composite electrode, the step 3 comprises: Step 3-1: Calculate the band structure and Fermi level of boron-doped diamond films with different boron doping amounts through first-principles calculations, select a metal with a Fermi level close to that of boron-doped diamond to achieve ohmic contact, and select an appropriate doping amount and a metal that matches its energy level to improve the electrical properties of the composite electrode; Step 3-2: Using a magnetron sputtering device, controlling the sputtering power and deposition time, and depositing a metal film with energy level matching on the surface of the processed boron-doped diamond film; Step 3-3: Spheroidize the metal layer into nano-metal balls through high-temperature heat treatment in a protective atmosphere or vacuum, embed the nano-metal ball particles into the microstructure, and obtain a smooth structural surface by controlling the thickness of the metal layer and the annealing temperature.
[0014] The method for preparing the boron-doped diamond film / metal composite electrode, wherein in step 3-2, any one of titanium, silver, platinum or gold is used as the filler metal, comprises: Step a: using magnetron sputtering equipment, first deposit a 10-20 nm thick metal film layer; Step b: heating at 600-800° C. in a protective atmosphere or vacuum to spheroidize the metal film layer into nano-metal spheres, so that the nano-metal sphere particles are embedded in the microstructure; Step c: annealing in a protective atmosphere or vacuum, and repeating steps ab until a smooth structure surface is formed and the boron-doped diamond film is not completely covered.
[0015] A boron-doped diamond film / metal composite electrode, the composite electrode comprising a smoothing layer, a deposition layer, a microstructure layer, and a substrate, the microstructure layer being formed by etching the substrate surface and removing the non-diamond carbon on the surface, the deposition layer being deposited on the microstructure layer by a magnetron sputtering device and being bonded to the microstructure layer, and the deposition layer being subjected to high-temperature heat treatment to obtain the smoothing layer having a smooth surface.
[0016] The boron-doped diamond film / metal composite electrode and the preparation method thereof of the present invention have the following beneficial effects: compared with the prior art which often adopts a method of increasing the boron doping amount in order to improve the conductivity of the boron-doped diamond film, but in the preparation of the heavily boron-doped diamond film, non-diamond carbon is inevitably generated, which affects the stability of the electrode; the technical solution provided by the present invention regulates the non-diamond carbon content and its distribution during the film growth process, and then removes the non-diamond carbon on the surface by etching, thereby eliminating the influence of the non-diamond carbon on the long-term stability of the electrode; in the prior art, the surface of the boron-doped diamond film electrode commonly used in the salinity sensor is relatively rough, which will produce long-term drift during salinity monitoring and is easily attached by microorganisms; the technical solution finds the matching boron doping concentration and contact metal through the band structure of the semiconductor-metal contact interface of the composite electrode, and deposits the metal film on the treated electrode surface, which can not only improve the carrier concentration of the electrode, but also reduce the contact resistance between the electrode and the lead metal, thereby solving the problem of the boron-doped diamond film electrode in the high-precision measurement of ocean salinity. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a diagram showing the initial state of boron doped into a diamond film in an embodiment of the present invention; Figure 2 Schematic diagram of the microstructure layer after etching in an embodiment of the present invention; Figure 3 This is a schematic diagram after a layer of metal is deposited in an embodiment of the present invention; Figure 4 This is a schematic diagram of multiple depositions and annealing in an embodiment of the present invention; Figure 5 A schematic diagram of the composite electrode structure in an embodiment of the present invention; Figure 6 Flow chart of the preparation method in the embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is described below in conjunction with specific implementation methods and drawings.
[0019] Example 1 like Figure 6 As shown, a method for preparing a boron-doped diamond film / metal composite electrode includes the following steps.
[0020] Step 1: Preparation of heavily boron-doped diamond film, using hot wire chemical vapor deposition equipment to adjust growth parameters, and after a certain growth time, obtain a heavily boron-doped diamond film with controllable surface non-diamond carbon content.
[0021] include: Step 1-1: Clean the hot wire chemical vapor deposition equipment chamber, place the tantalum wire on the bracket, place the substrate on the base plate, close the chamber, and evacuate to below 10Pa.
[0022] Step 1-2: Adjust the amount of methane and hydrogen introduced into the chamber to carbonize the tantalum wire.
[0023] Step 1-3: Adjust the flow ratio of trimethylborane and methane into the chamber, maintain the pressure balance in the chamber, maintain the flow of hydrogen, control the growth temperature at 850-900° C., and grow the boron-doped diamond film in the chamber.
[0024] Step 1-4: reducing the hydrogen flow rate to obtain a heavily boron-doped diamond film containing non-diamond carbon on the surface.
[0025] Step 2: Treat the surface of the heavily boron-doped diamond film by immersion treatment and / or etching treatment, and remove non-diamond carbon by etching to obtain a boron-doped diamond film with a surface microstructure.
[0026] The immersion treatment method includes: Step 2-1: Acid mixing: Mix concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1 to 1:3 and heat to 260-300°C.
[0027] Step 2-2: Soaking treatment: soak the grown boron-doped diamond film in a mixed acid solution of sulfuric acid and nitric acid for 2-4 hours, generally about 3 hours, to remove non-diamond carbon on the surface.
[0028] Step 2-3: Surface cleaning: soak the soaked boron-doped diamond film in deionized water, treat it with an ultrasonic cleaner for 20-40 minutes, and blow dry it with nitrogen to obtain a boron-doped diamond film with a surface microstructure.
[0029] The etching treatment method includes: placing a heavily boron-doped diamond film into a plasma etcher, introducing oxygen and argon into the plasma etcher, with the flow ratio of oxygen to argon being 5:1 to 10:1, adjusting the power of the plasma etcher, and treating for 10-30 minutes to remove non-diamond carbon on the surface of the heavily boron-doped diamond film to form a boron-doped diamond film with a microstructure on the surface.
[0030] Step 3: Energy level matching metal fills the surface microstructure, calculates the energy band structure of the boron doped diamond film and the energy level matching with the metal, deposits an energy level matching metal film on the surface of the boron doped diamond film with surface microstructure and performs high temperature heat treatment to obtain a boron diamond metal composite electrode with a smooth structure surface.
[0031] include: Step 3-1: Calculate the band structure and Fermi level of boron-doped diamond films with different boron doping amounts through first-principles calculations, and select a metal with a Fermi level close to that of boron-doped diamond to achieve ohmic contact. The appropriate doping amount and a metal that matches its energy level can be selected to improve the electrical properties of the composite electrode.
[0032] Step 3-2: Using magnetron sputtering equipment, control the sputtering power and deposition time to deposit a metal film with energy level matching on the surface of the processed boron-doped diamond film.
[0033] include: Step a: Using magnetron sputtering equipment, first deposit a layer of one of metal titanium, silver, platinum or gold with a thickness of 10-20nm.
[0034] Step b: heating to 600-800° C. in a protective atmosphere or vacuum to spheroidize the metal layer into nano-metal spheres, and embed the nano-metal sphere particles into the microstructure.
[0035] Step c: If the surface microstructure is not filled, a layer of the same metal as in step a with a thickness of 10-20 nm is deposited using a magnetron sputtering device.
[0036] Step d: annealing at 600-800° C. in a protective atmosphere or vacuum, and repeating steps ab until a smooth structure surface is formed and the surface is not completely covered with the boron-doped diamond film.
[0037] Step 3-3: Spheroidize the metal layer into nano-metal balls through high-temperature heat treatment in a protective atmosphere or vacuum, embed the nano-metal ball particles into the microstructure, and obtain a smooth structural surface by controlling the thickness of the metal layer and the annealing temperature.
[0038] Example 2 A method for preparing a boron-doped diamond film / metal composite electrode includes the following aspects.
[0039] 1. Preparation of heavily boron-doped diamond films.
[0040] The boron-doped diamond film is prepared by hot-wire chemical vapor deposition equipment, with methane, trimethylborane and hydrogen introduced during the growth, and grown at a certain growth temperature and gas pressure.
[0041] The doping amount is controlled by adjusting the ratio of borane to methane to prepare a doping concentration of 8000-20000 ppm (heavy doping); the etching of non-diamond carbon by hydrogen during the growth process is regulated by adjusting the hydrogen content to ensure the quality and purity of the boron-doped diamond film inside the film; the growth rate and film quality are regulated by adjusting the gas pressure; and the deposition temperature is controlled to control the amount of non-diamond carbon deposited on the surface.
[0042] After a certain growth period, a heavily boron-doped diamond film with controllable surface non-diamond carbon content is obtained, such as Figure 1 shown.
[0043] The specific steps include: 1. Clean the hot wire chemical vapor deposition equipment chamber, place the tantalum wire on the bracket, place the substrate on the base plate, close the chamber, and evacuate to below 10Pa.
[0044] 2. Introduce 20 sccm of methane and 500 sccm of hydrogen to carbonize the tantalum wire.
[0045] 3. Trimethylborane was introduced, and the flow ratio of trimethylborane to methane was set to 1:50 to 1:125. The gas pressure was maintained at 3-5 kPa, the hydrogen flow was maintained at about 500 sccm, and the growth temperature was controlled at 850-900 °C to ensure the quality and purity of the boron-doped diamond film inside the film. The growth time was about 6 hours.
[0046] 4. The gas flow rate is reduced to 300-400 sccm and maintained for 20 minutes to obtain a heavily boron-doped diamond film containing non-diamond carbon on the surface, with a doping amount of 8000-20000 ppm.
[0047] 2. Etching and removal of non-diamond carbon on the surface of heavily boron-doped diamond.
[0048] Immersion etching: The grown heavily boron-doped diamond film is placed in a sulfuric acid and nitric acid mixed acid solution and heated. By adjusting the etching solution concentration and heating temperature, the appropriate conditions for removing non-diamond carbon are selected. After the etching is completed, the boron-doped diamond film is immersed in deionized water and treated with an ultrasonic cleaner, and dried with nitrogen to obtain a boron-doped diamond film with a surface microstructure, such as Figure 2 shown.
[0049] Plasma etching: The surface of the heavily boron-doped diamond film is etched using a plasma etcher. By adjusting the etching time and power, the non-diamond carbon on the surface is mainly removed to form a boron-doped diamond film with a microstructure on the surface, such as Figure 2 shown.
[0050] The above two etching methods can be used interchangeably or separately, and are mainly used to obtain boron-doped diamond films with microstructures on the surface.
[0051] 3. Energy level matching metal-filled surface microstructure.
[0052] 1. Using the first-principles calculation method based on density functional theory, the microscopic film of the composite electrode is established using the Visualizer module of Materials Studio. The theoretical calculation method will use the generalized gradient approximation (GGA) and PBE (Perdew, Burke and Ernzerhof) functionals, and the basis set is configured as double numerical plus polarization (DNP). All structural optimization and property calculations are performed in the DFT framework based on the DMol3 module. The band structure of boron-doped diamond films with different boron doping amounts and the energy level matching with metals are calculated at the atomic scale, and the appropriate doping amount and metal are selected to improve the electrical properties of the composite electrode.
[0053] 2. Using magnetron sputtering equipment, a metal film with energy level matching is deposited on the surface of the processed boron-doped diamond film. By controlling the sputtering power and deposition time, a thickness between 10-50 nm is obtained.
[0054] In order to reduce the contact resistance between boron-doped diamond and metal, one of titanium, silver, platinum or gold is selected as the filling metal.
[0055] Using magnetron sputtering equipment, first deposit a 10-20nm thick layer of one of the metals titanium, silver, platinum or gold, such as Figure 3 shown.
[0056] 3. Heat to 600-800℃ in a protective atmosphere or vacuum to spheroidize the metal layer into nano-metal spheres, so that the nano-metal sphere particles are embedded in the microstructure, such as Figure 4 Repeat the above steps, control the thickness of the metal layer and the annealing temperature, until a smooth structure surface is formed and the boron-doped diamond film is not completely covered, as shown in FIG. Figure 5 shown.
[0057] 4. Test the electrical and ocean salinity sensing performance of boron-doped diamond thin films, and test the conductivity, contact resistance and electrical properties of boron-diamond metal composite electrodes.
[0058] 1. The conductivity of ordinary boron-doped diamond film electrodes and treated heavily doped diamond film / metal composite electrodes was measured using a four-probe measuring instrument.
[0059] 2. Use a probe station to measure the contact resistance between boron-doped diamond film and metal.
[0060] 3. Using an electrochemical workstation, with the boron-doped diamond film / metal composite electrode as the working electrode and metal platinum as the counter electrode, the electrical properties of the boron-doped diamond film / metal electrode were analyzed.
[0061] Example 3 like Figure 5 As shown, a boron-doped diamond film / metal composite electrode includes a smoothing layer 4, a deposition layer 3, a microstructure layer 2, and a substrate 1. The substrate is a boron-doped diamond film. The microstructure layer is formed by etching the substrate surface and removing the surface non-diamond carbon 5. The deposition layer is deposited on the microstructure layer by a magnetron sputtering device and is bonded to the microstructure layer. The deposition layer is subjected to high-temperature heat treatment to obtain a smoothing layer with a smooth surface.
[0062] The deposited layer mainly comprises one of metal titanium, silver, platinum or gold. The metal layer is subjected to high temperature heat treatment to form a smooth layer with a smooth surface.
[0063] The non-diamond carbon content and distribution are controlled during the film growth process, and then the non-diamond carbon is removed by etching to obtain a microstructure layer. A magnetron sputtering device is used to deposit metal on the microstructure layer in small amounts and multiple times. After annealing, the metal is completely attached to the microstructure layer to fill the concave shape formed by the non-diamond carbon. Metal is deposited multiple times on the outer surface of titanium and the ductility of the metal is utilized. A smooth electrode surface structure is obtained through high-temperature treatment, thereby eliminating the influence of non-diamond carbon on the long-term stability of the electrode.
[0064] By finding the matching boron doping concentration and contact metal through the energy band structure of the composite electrode semiconductor-metal contact interface, and depositing the metal film on the treated electrode surface, not only can the carrier concentration of the electrode be increased, but also the contact resistance between the electrode and the lead metal can be reduced, thus solving the problem of boron-doped diamond film electrodes in high-precision measurement of ocean salinity.
[0065] The above embodiments are only for illustrating the inventive concept and features of the present invention, and their purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a boron-doped diamond film / metal composite electrode, characterized in that: The following steps are involved: Step 1: Preparation of heavily boron-doped diamond film, using hot wire chemical vapor deposition equipment to adjust growth parameters, and after a certain growth time, obtain a heavily boron-doped diamond film containing non-diamond carbon on the surface; Step 2: treating the surface of the heavily boron-doped diamond film, removing non-diamond carbon by etching, and obtaining a boron-doped diamond film with a surface microstructure; Step 3: Energy level matching metal fills the surface microstructure, calculates the energy band structure of the boron doped diamond film and the energy level matching with the metal, deposits an energy level matching metal film on the surface of the boron doped diamond film with surface microstructure and performs high temperature heat treatment to obtain a boron doped diamond film / metal composite electrode with a smooth structure surface.
2. The boron-doped diamond film / metal composite electrode and its preparation method according to claim 1, characterized in that: It also includes step 4: electrical and ocean salinity sensing performance testing of the boron-doped diamond film / metal composite electrode, testing the conductivity, contact resistance, and electrical performance of the boron-doped diamond film / metal composite electrode.
3. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 2, characterized in that: The conductivity of the boron-doped diamond film / metal composite electrode is measured by a four-probe measuring instrument; the contact resistance between the boron-doped diamond film / metal composite electrode and the metal is measured by a probe station; and the electrical properties of the boron-doped diamond film / metal composite electrode are analyzed by an electrochemical workstation with the boron-doped diamond film / metal composite electrode as a working electrode and metal platinum as a counter electrode.
4. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 1, characterized in that: The step 1 comprises: Step 1-1: Clean the hot wire chemical vapor deposition equipment chamber, place the tantalum wire on the bracket, place the substrate on the base plate, close the chamber, and evacuate to below 10Pa; Step 1-2: adjusting the amount of methane and hydrogen introduced into the chamber to carbonize the tantalum wire; Step 1-3: adjusting the flow ratio of trimethylborane to methane into the chamber, maintaining the pressure balance in the chamber, maintaining the flow rate of hydrogen, controlling the growth temperature at 850-900° C., and growing a heavily boron-doped diamond film in the chamber; Step 1-4: reducing the hydrogen flow rate to obtain a heavily boron-doped diamond film containing non-diamond carbon on the surface.
5. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 1, characterized in that: The step 2 of treating the surface of the heavily boron-doped diamond film comprises an immersion treatment method and / or an etching treatment method.
6. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 5, characterized in that: The immersion treatment method comprises: Step 2-1: Acid mixing: Mix concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1 to 1:3, and heat to 260-300°C; Step 2-2: soaking treatment, soaking the grown boron-doped diamond film in a sulfuric acid and nitric acid mixed acid solution for 2-4 hours to remove non-diamond carbon on the surface; Step 2-3: Surface cleaning: soak the soaked boron-doped diamond film in deionized water, treat it with an ultrasonic cleaner for 20-40 minutes, and blow dry it with nitrogen to obtain a boron-doped diamond film with a surface microstructure.
7. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 5, characterized in that: The etching treatment method comprises: placing a heavily boron-doped diamond film into a plasma etcher, introducing oxygen and argon into the plasma etcher, wherein the flow ratio of oxygen to argon is 5:1 to 10:1, adjusting the power of the plasma etcher, and treating for 10-30 minutes to remove non-diamond carbon on the surface of the heavily boron-doped diamond film to form a boron-doped diamond film with a microstructure on the surface.
8. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 1, characterized in that: The step 3 comprises: Step 3-1: Calculate the band structure and Fermi level of boron-doped diamond films with different boron doping amounts through first-principles calculations, select a metal with a Fermi level close to that of boron-doped diamond to achieve ohmic contact, and select an appropriate doping amount and a metal that matches its energy level to improve the electrical properties of the composite electrode; Step 3-2: Using a magnetron sputtering device, controlling the sputtering power and deposition time, and depositing a metal film with energy level matching on the surface of the processed boron-doped diamond film; Step 3-3: Spheroidize the metal layer into nano-metal balls through high-temperature heat treatment in a protective atmosphere or vacuum, embed the nano-metal ball particles into the microstructure, and obtain a smooth structural surface by controlling the thickness of the metal layer and the annealing temperature.
9. The boron-doped diamond film / metal composite electrode and the preparation method thereof according to claim 8, characterized in that: In step 3-2, any one of titanium, silver, platinum or gold is used as the filler metal, including: Step a: using magnetron sputtering equipment, first deposit a 10-20 nm thick metal film layer; Step b: heating at 600-800° C. in a protective atmosphere or vacuum to spheroidize the metal film layer into nano-metal spheres, so that the nano-metal sphere particles are embedded in the microstructure; Step c: annealing in a protective atmosphere or vacuum, and repeating steps ab until a smooth structure surface is formed and the boron-doped diamond film is not completely covered.
10. A boron-doped diamond film / metal composite electrode, characterized in that: The composite electrode includes a smoothing layer, a deposition layer, a microstructure layer, and a substrate. The microstructure layer is formed by etching the substrate and removing the non-diamond carbon on the surface. The deposition layer is deposited on the microstructure layer using a magnetron sputtering device and adhered to the microstructure layer. The deposition layer is subjected to high-temperature heat treatment to obtain the smoothing layer with a smooth surface.